The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1172/jci115136
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid storage diseases. A multiple lysosomal transport defect for acidic monosaccharides.

Abstract: A defective efflux of free sialic acid from the lysosomal compartment has been found in the clinically heterogeneous group of sialic acid storage disorders. Using radiolabeled sialic acid (NeuAc) as a substrate, we have recently detected and characterized a proton-driven carrier for sialic acid in the lysosomal membrane from rat liver. This carrier also recognizes and transports other acidic monosaccharides, among which are uronic acids. If no alternative routes of glucuronic acid transport exist, the disposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 39 publications
3
40
0
1
Order By: Relevance
“…Compared with ISSD, Salla disease is clinically less severe and is associated with lower levels of free sialic acid in both urine and cells cultured from patients. An unresolved issue has been the difference in phenotypes for Salla disease and ISSD, despite a complete absence of measurable sialic acid transport activity in lysosomes derived from patients with both diseases (15,16,27). Although this has been attributed to a lack of sensitivity in the methods used to measure lysosmal transport activity, some uncertainty has persisted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with ISSD, Salla disease is clinically less severe and is associated with lower levels of free sialic acid in both urine and cells cultured from patients. An unresolved issue has been the difference in phenotypes for Salla disease and ISSD, despite a complete absence of measurable sialic acid transport activity in lysosomes derived from patients with both diseases (15,16,27). Although this has been attributed to a lack of sensitivity in the methods used to measure lysosmal transport activity, some uncertainty has persisted.…”
Section: Discussionmentioning
confidence: 99%
“…Although a partial reduction in transport activity could lead to disease, the absence of a phenotype in heterozygote carriers of the free sialic acid storage disorders, who have approximately half the normal lysosomal sialic acid transport activity (27), suggests that activity would need to be reduced by more than 50%. Therefore, we wanted to know, more precisely, the effect of the R39C and K136E mutations on activity.…”
Section: Disruption Of Putative Adaptor Protein-binding Domain Leads mentioning
confidence: 99%
“…The two main clinical phenotypes are Salla or adult-type disease presenting with mental retardation, ataxia, and normal life span and ISSD with early-onset psychomotor retardation, coarse facies, hepatosplenomegaly and death early in childhood. Both disorders are probably a gradation of the same defect that appears to involve impairment of an active proton-driven and substrate-specific transport system of free sialic acid across the lysosomal membrane [Mancini et al, 1989[Mancini et al, , 1991Tietze et al, 1989]. The end result is an accumulation of free sialic acid within the lysosome.…”
Section: Introductionmentioning
confidence: 99%
“…In ISSD and Salla disease, a defect in sialin activity has been shown (Mancini et al 1991). So, a large amount of free sialic acid residues must be accumulated in lysosomes, and this might secondarily cause a defect in the catalytic metabolism of sialyl glycoconjugates in lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…They are caused by impaired anion transport across the lysosomal membrane (Mancini et al 1991), and the responsible gene has been identified as the SLC17A5-gene (Verheijen et al 1999;Aula et al 2000) located on the long arm of chromosome 6.…”
Section: Introductionmentioning
confidence: 99%